Inhibition of fungal deterioration of stored pigeonpea seeds by Cuminum cyminum oil - and N.N. TRIPATHI*, VANDANA PANDEY, NARENDRA KUMAR (Indian Phytopathology, 2007)
Stored seed samples of pigeonpea collected from 18 places of Eastern Uttar Pradesh, India were examined for associated fungi. Seventeen fungal species were associated with the seed samples. Out of these, Aspergillus flavus and A. niger were predominant and caused heavy deterioration in fresh seeds. Volatile constituents extracted in the form of essential oils from 50 higher plants were evaluated against these two fungi. The oil from cumin (Cuminum cyminum) caused cent percent inhibition. The oil of cumin protected seeds of pigeonpea for six months stored in 250 g plastic-gunny bags. It was found superior over the synthetic fumigants tried. The oil did not exhibit any adverse effect on seed germination (showed 86.6 to 93.3 germination), seedling growth, general health and morphology of host plants. Thus the cumin oil can be judiciously used as botanical preservative for pigeonpea seeds against spoilage by fungi during storage.